Analisis Perbedaan Tingkat Efisiensi Bank Umum Syariah dan Bank Umum Konvensional di Indonesia melalui Pendekatan Data Envelopment Analysis (DEA) Periode 2020-2022 - Aisyah Ramadani, Nur; Bakhtiar, Fauzia (Study of Scientific and Behavioral Management, 2024)
This research aims to determine the differences in the efficiency levels of Sharia Commercial Banks and Conventional Commercial Banks through the Data Envelopment Analysis (DEA) approach of the CRS & VRS model, as well as the dominant variables and sub-variables that influence the differences in efficiency of Sharia Commercial Banks and Conventional Commercial Banks in Indonesia for the period 2020- 2022. This research uses quantitative research methods. This research uses secondary data, namely financial reports from each Sharia Commercial Bank and Conventional Commercial Bank in Indonesia for the 2020-2022 period. Based on the results of the research that has been carried out, there are differences in the efficiency levels of Sharia Commercial Banks and Conventional Commercial Banks using the DEA CRS and VRS model approaches which produce higher efficiency values ​​for Sharia Commercial Banks compared to Conventional Commercial Banks. The results of calculating the efficiency level based on the CRS model resulted in the highest average efficiency level obtained by Sharia Commercial Banks of 98%. Meanwhile, the level of efficiency obtained by Conventional Commercial Banks is 90%. Meanwhile, based on the VRS model, the highest average efficiency level obtained by Sharia Commercial Banks was 99%. Meanwhile, the level of efficiency obtained by Conventional Commercial Banks is 91%. The difference in efficiency levels of Sharia Commercial Banks and Conventional Commercial Banks is predominantly influenced by input variables, especially operational costs. Keywords: Data Envelopment Analysis (DEA), Constant Return to Scale (CRS), Variable Return to Scale (VRS)